Political Roles of Women in the Legislative and Presidential Election - Anita Dhewy (Jurnal Perempuan, 2014)
Female representation in parliament is decreasing in 2014, from 18 to 17 percent. This is not good news at all. It deteriorates further with no focus on women’s status in each of presidential candidates. Status of women, sexual minorities, and other vulnerable groups were not becoming focus of issues in debates. Women’s movement in near future and in the long run shall fight hard to tackle previous problems. This 2014 General Election has been a powerful tool as well for women to participate and to voice their concern regarding issues of equality and justice. This study unearths how women usher peaceful campaign during the parliament and presidential elections—showing their political engagement to Indonesia as democratic state.